Investigations of defects in Pb(Mg1/3Nb2/3)O3-PbTiO3 single crystals grown along [001] direction. Issue 10 (July 2019) - Zhu, Rongfeng; Li, Xiaobing; Fu, Zhengqian; Chen, Jianwei; Xu, Haiqing; Luo, Haosu
Abstract: The defects of the [001]-oriented grown 0.73Pb(Mg1/3 Nb2/3 )O3 -0.27PbTiO3 (PMN-0.27PT) single crystals, as well as their influence on electrical properties, were studied by comparing the as-grown and annealed samples. Apart from the anomalies induced by the successive ferroelectric phase transitions, four relaxation processes of the as-grown PMN-0.27PT single crystals grown along [001] direction were discussed and determined by the dielectric spectroscopy, complex impedance spectroscopy, AC conductivity, suggesting the existence of many oxygen vacancies and lead vacancies in the as-grown samples. High-angle annular dark-field imaging of scanning transmission electron microscope (HAADF-STEM) was applied to observe the defects in atomic-scale. The point defects generated more easily when growing the PMNT crystals along [001] direction than along [111] direction can be attributed to the difference of growth mechanism and necessary growth environment induced by different growth directions, which results in the special coloration phenomenon of the [001]-oriented grown PMNT crystals.